DAMPAK SOSIAL EKONOMI PENATAAN DAN PEMBERDAYAAN PEDAGANG KAKI LIMA DI PANTAI PADANG - Putri, Risya Nurya Ayyu; Azwar, Welhendri; Jamil, Muhammad (Universitas Islam Indonesia, 2024)
This research examines the social and economic impacts of the arrangement of street vendors (PKL) in Padang Beach, especially related to relocation and restrictions on selling time. The research used descriptive qualitative methods with observation and in-depth interviews. The results show that the arrangement is often detrimental to the street vendors, resulting in decreased income and dissatisfaction due to the less strategic new location. Despite government promises to provide adequate facilities, many street vendors feel these promises are not realized, which adds to social unrest and distrust of the government. Conflicts between street vendors and the government arise in the social aspect, while the economy of street vendors experiences a significant drop in income, especially for those who depend on crowded locations. The results show that the arrangement is often detrimental to the street vendors, resulting in decreased income and dissatisfaction due to the new, less strategic location. Overall, the arrangement of street vendors in Pantai Padang has not been successful, so further evaluation is needed to improve the welfare of traders and provide guidance for policymakers in designing more inclusive street vendor empowerment strategies.